A predator–prey model of knowledge spillovers and entrepreneurship - Parker, Simon C. (Strategic Entrepreneurship Journal, 2010)
Abstract Knowledge spillovers are known to generate positive benefits for entrepreneurs, but may come at the expense of knowledge creation by the incumbent firms which generate them. This article develops a predator–prey model of knowledge spillovers which captures the interdependence between idea‐creating incumbents and knowledge spillover‐appropriating entrepreneurs. The values of the model's parameters determine whether these two populations of firms settle down in a stable equilibrium; cycle over time with entrepreneurs doing well when incumbents do badly and vice‐versa; or drive each other to extinction. This sheds light on disparate industry life cycle patterns observed in previous research and generates some novel insights relating to public policy. In particular, the model suggests that governments ought to adopt a dynamic policy stance, initially implementing policies which favor incumbents before shifting their intervention efforts toward encouraging entrepreneurs. Copyright © 2010 Strategic Management Society.